1979
DOI: 10.1007/bf00569354
|View full text |Cite
|
Sign up to set email alerts
|

Associations between atopic diseases and the polymorphic systems ABO, kidd, inv and red cell acid phosphatase

Abstract: In 239 German patients with atopic conditions (atopic dermatitis, hay fever, allergic rhinitis, bronchial asthma, and acute urticaria) the phenotype and gene distribution of 15 genetic blood polymorphisms (ABO, MNSs, rhesus, P, Kell, Duffy, Kidd, Hp, Gc, Gm, Inv, aP, PGM1, EsD, and 6-PGD) were analyzed and compared with those in 151 selected controls (individuals clinically free of allergic conditions and without allergy in the family history). The incidence of blood group antigens A and B was somewhat higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 7 publications
3
17
1
Order By: Relevance
“…A study conducted in Germany reported the higher incidence of blood group antigens A and B in patients with atopic diseases (atopic dermatitis, hay fever, allergic rhinitis, bronchial asthma, and acute urticaria) in comparison with controls (individuals clinically free of allergic conditions and without allergy in the family history) (9). Several studies suggest that there is an association between specific ABO blood types and some medical conditions commonly associated with NP (4-6, 10).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Germany reported the higher incidence of blood group antigens A and B in patients with atopic diseases (atopic dermatitis, hay fever, allergic rhinitis, bronchial asthma, and acute urticaria) in comparison with controls (individuals clinically free of allergic conditions and without allergy in the family history) (9). Several studies suggest that there is an association between specific ABO blood types and some medical conditions commonly associated with NP (4-6, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier investigations of genetic markers in atopy have shown a preponderance of Km( 1 ) [4], the marker for the k light chain of immunoglobulins. In atopic patients an imbalanced IgG subclass pattern with increased IgG4 is common [9,12,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In atopy an association has been found to the allo type Km(l) for k light chains of the immunoglobulins on chromosome 2 [4], Earlier investigations did not reveal any deviation from normal as to Gm allotypes, but the G2m(n) allotype was not investigated. Re cently produced monoclonal antibodies to G2m(n) were used to investigate atopic patients, known to have the characteristic imbalanced IgG subclass pat tern with increased IgG4.…”
Section: Introductionmentioning
confidence: 99%
“…One such study found statistically significant differences in the frequencies of the ABO and related secretor phenotypes in Australian adults (6) and another reported a greater incidence of A and B red blood cell phenotypes in patients with different atopical conditions compared to controls. (7) Associations between the ABO and Secretor systems and asthma have also been observed in Italian (8) and Taiwanese children (9) but not in Indian adults. (10) Despite these contradictory results observed among patients suffering from asthma, studies associating these genetic markers with allergic rhinitis are scarce.…”
Section: Introductionmentioning
confidence: 98%